Tamarind seed extract enhances epidermal wound healing - Mohamad, Mohd Yusuf; Akram, Haris B.; Bero, Dinie Najwa; Rahman, Mohammad Tariqur (2010)
Traditional healing power of tamarind fruits and the established antioxidant activity of the seeds drive the present study. Present study was done to evaluate the efficiency of wound healing. 10ug of 5ug/ml of extract was administered to female ICR-type mice. Surface area of the wound was measured using adobe Photoshop C3 Extended version and the percentage of reduction was calculated. Different types of solvent namely Phosphate Buffer saline (PBS), water, methanol and ethanol were used as the extraction solvents. PBS extract (PE) treatment induced complete wound healing in shortest period (10 days); water extract treatment (WE), methanol extract treatment (ME) and Solcoseryl ointment in 11 days and sterile deonized water in 14 days. Phytochemical screening and Bradford method were performed to detect chemical compound qualitative and quantitatively. Alkaloid and saponin were tested positive in all samples. Only methanol and ethanol extract gave positive result on flavonoid testing. Tannin was detected in all samples except PBS extract. The effective yield of ethanol extraction was shown in the study.